Methods for groundwater natural recharge in a small watershed a comparative study (Research, Society and Development, 2020)
The percentage of precipitation that supplies the aquifers is essential for management of groundwater resources. This research presents an evaluation of the groundwater natural recharge in the small watershed of Uriboquinha creek, located in Marituba, Pará. The watershed has an area of 5 km² and, it made part of the Planning Unit Acará-Guamá. Estimates were made for a period from September 2018 to August 2019 based on two methods: Water Table Fluctuations (WTF) and Direct Potential Recharge (DPR). For the first, fourteen monitoring wells from the sanitary landfill located in Marituba-PA were used, while for the second, precipitation data from a rainfall station in Belém-PA and regionalized runoff data were used. The results obtained for the WTF method varied, well to well, between 1.2% to 26.5%, with an average value of 9.8%, equivalent to 378.9 mm, considering total precipitation of 3,866.8 mm during the study time, while for the DPR method, a rate of 6% was obtained, equivalent to 232 mm. The first method indicated an existing spatial variability in the study area, providing information on the hydraulic gradient and groundwater flow direction, indicated for studies with more precision in the recharge. While the second is more suitable for regulatory and water resource management purposes, providing a more conservative scenario.